2020
DOI: 10.1016/j.apergo.2020.103063
|View full text |Cite
|
Sign up to set email alerts
|

Journey mapping from a crew's perspective: Understanding rail experiences

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…According to the theory, the tea-brewing experience can be improved by further enhancing the most positive experience, addressing the worst experience during the tea-brewing process, and improving the immediate feelings of customers at the end of the service. CJM is a commonly used user-centric industry method [26] for visualizing customer service experiences [27][28][29][30]. In CJM, customer activities are divided into steps, stages, touchpoints, customer emotions, and pain-points [31].…”
Section: Research Methodology For the Tea Brewing Experimentsmentioning
confidence: 99%
“…According to the theory, the tea-brewing experience can be improved by further enhancing the most positive experience, addressing the worst experience during the tea-brewing process, and improving the immediate feelings of customers at the end of the service. CJM is a commonly used user-centric industry method [26] for visualizing customer service experiences [27][28][29][30]. In CJM, customer activities are divided into steps, stages, touchpoints, customer emotions, and pain-points [31].…”
Section: Research Methodology For the Tea Brewing Experimentsmentioning
confidence: 99%
“…In the case of the rail industry, little is known about how train staff perceive their current journeys, and how the introduction of new technology would be received into this environment. The rare studies evaluating crew experiences when facing new technology consider the workforce as a single type of user (Oliveira et al, 2020). With the current study we suggest the need to define who they are, how they interact with current systems and the potential impact of the new technology.…”
Section: Introductionmentioning
confidence: 93%
“…Customer-facing onboard crew engage directly with passengers, and this interaction can sometimes be emotionally demanding (Maria Stock et al, 2017;Oliveira et al, 2020). Crew are often subject to abuse from passengers (Salomonson and Fellesson, 2014), which can affect health and reduce job satisfaction (Boyd, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the modernization of transport, the role of the human factor remains signi cant [2]. It is reported that from a psychological point of view, the most stressful experience for members of train crews is moving alongside platforms [3]. Different types of psychological responses to workloads are described in a number of publications [4].…”
Section: Introductionmentioning
confidence: 99%